EVALUASI KOMPETENSI BIDAN DALAM PEMASANGAN ALAT KONTRASEPSI DALAM RAHIM COPPER T 380A BERDASARKAN UMUR, PENDIDIKAN, PENGALAMAN PEMASANGAN DAN LAMA PRAKTIK DI KOTA PADANG - Desmiwarti, Desmiwarti; Bachtiar, Hafni (Fakultas Kedokteran Universitas Andalas, 2019)
Midwives are health providers influential in helping families to choose appropriate contraception for patients. Midwives must have competence in providing midwifery services in particular IUD insertion. This study’s aim was to evaluate the competency of midwives in the insertion of an intrauterine device Copper T 380A based on their age, education, experience of insertion and duration of practice in Padang City. This study was done in puskesmas and private midwivery practice in Padang from September to December 2014 using cross-sectional method on 24 samples who met the inclusion criteria and not exclusion criteria. We conducted interviews and observed how the respondents perform IUD insertion by using a check- list. From this study, there was no significant association between age (p: 0.540, p> 0.05), education (p: 0.439, p> 0.05), experience of insertion (p: 0.472, p> 0.05) and duration of practice (p: 0.505, p> 0.05) with competency of IUD insertion. Most respondents have a good competence in IUD insertion. Part of the checklist the respondents frequently missed out were conseling to the patients and prevention of infection.Keywords: Midwives Competency, IUD insertion, Copper T-380a